Revised Phylogeny of the Cellulose Synthase Gene Superfamily: Insights into Cell Wall Evolution. Issue 3 (18th May 2018) - Little, Alan; Schwerdt, Julian G.; Shirley, Neil J.; Khor, Shi F.; Neumann, Kylie; O'Donovan, Lisa A.; Lahnstein, Jelle; Collins, Helen M.; Henderson, Marilyn; Fincher, Geoffrey B.; Burton, Rachel A.
Abstract : Sequenced genomes of land plants enabled a renewal of cellulose synthase gene superfamily phylogeny, which revealed a previously unknown eudicot lineage, CslM, and showed that (1, 3;1, 4)-β-glucan synthesis is not restricted to the Poaceae. Abstract: Cell walls are crucial for the integrity and function of all land plants and are of central importance in human health, livestock production, and as a source of renewable bioenergy. Many enzymes that mediate the biosynthesis of cell wall polysaccharides are encoded by members of the large cellulose synthase ( CesA ) gene superfamily. Here, we analyzed 29 sequenced genomes and 17 transcriptomes to revise the phylogeny of the CesA gene superfamily in angiosperms. Our results identify ancestral gene clusters that predate the monocot-eudicot divergence and reveal several novel evolutionary observations, including the expansion of the Poaceae-specific cellulose synthase-like CslF family to the graminids and restiids and the characterization of a previously unreported eudicot lineage, CslM, that forms a reciprocally monophyletic eudicot-monocot grouping with the CslJ clade. The CslM lineage is widely distributed in eudicots, and the CslJ clade, which was thought previously to be restricted to the Poales, is widely distributed in monocots. Our analyses show that some members of the CslJ lineage, but not the newly identified CslM genes, are capable of directing (1, 3;1, 4)-β-glucan biosynthesis, which, contrary to current dogma, is not restricted to Poaceae.